Bias-stress-stable sub-1.5V oxide thin-film transistors via synergistic composition of sol-gel quaternary high-k oxide dielectrics - Baek, Seokhyeon; Choi, Jun Gyu; Lee, Won June; Kwak, Taehyun; Jo, Yong Ryun; Park, Sungjun (Journal of Alloys and Compounds, 2024)
A rising demand in reliable, energy-efficient, and large-area electronics, particularly in the realm of sol-gel oxide thin-film transistors (TFTs), has steered research focus away from semiconductor towards dielectrics. However, achieving both bias stability and low-voltage operation remains a significant hurdle. While typical oxide TFTs employ high-dielectric-constant (high-k) dielectrics with lowered film thickness to acquire low-voltage operation, they inevitably suffer from undesired defects at both bulk and interfacial trap sites in dielectric layer. In this study, bias-stress-stable all solution-processed oxide TFTs were demonstrated with operation voltage under 1.5 V via sol-gel quaternary high-k oxide dielectric (Al-Hf-Zr-O, AHZO). In-depth understanding of their individual contributions to dielectric performance leads to the acquisition of optimized composition ratios of AHZO with amorphous feature and outstanding dielectric performance, marked by dielectric constant (k) over 11, leakage current density (Jleak) below 10−5.5 A cm−2, and sturdy breakdown strength (EB) exceeding 5 MV cm−1. By integrating the AHZO with In-Ga-Zn-O (IGZO) layer, we achieved sub 1.5 V TFTs while maintaining excellent bias stability with threshold voltage (VTH) shift lower than 0.20 V for 3600 s. Our findings offer a detailed insight into the realm of multi-component oxide dielectrics, paving the way for miniaturization and reliability in functional devices and sensors.
Keywords: Bias stress; C. thin film transistor (TFT); Device reliability; High-k oxides; Oxide dielectric; Oxide thinfilm transistors (TFTs); Quaternary oxide film; Quaternary oxides; Sol'gel; Solution-processing; Device reliability; High-k dielectrics; Quaternary oxide films; Solution processing; Thin-film transistors